Tomografi Waktu Tempuh Gelombang S dan Struktur 3-D Zona Penunjaman di Bawah Busur Sunda - Sri Widiyantoro; Nanang T. Puspito (Jurnal Matematika & Sains, 1998)
Tomographic imaging by using S-wave traveltime data to deliniate the three-dimensional subduction zone structure below the Sunda arc has been successfully conducted. Most of the resulting S-wave velocity model is in good agreement with the results of previous tomographic studies using P-wave traveltime data. The obtained tomographic images show that the lithospheric slab penetrates into the lower mantle beneath the Sunda arc, but there is an indication that the deep slab is detached from the seismogenic slab underneath Sumatra and the slab in the upper mantle is necking beneath Java.